COMPARATIVE ANALYSIS OF PRODUCTION EFFICIENCY OF ORGANIC AND INORGANIC RICE FARMING - Annisa Ambarwati; Sucihatiningsih Dian Wisika Prajanti; Amin Pujiati (Universitas Negeri Semarang, 2026)
Production efficiency is a benchmark used to determine whether a production activity is running well so that it can achieve maximum profits.This research aims to analyze production levels, factors that influence organic and inorganic rice production results and analyze the level of efficiency. This study uses a quantitative approach. The population in this study were organic and inorganic rice farmers in Sawit District. Determining the sample in this research uses the method simple random sampling with a total sample of 59 organic farmers and 59 inorganic farmers. Data collection techniques use interviews. The data analysis technique used is production analysis using the Cobb-Douglas production function with multiple linear regression. Technical efficiency analysis uses a frontier production function withStochastic Frontier Analysis (SFA). Allocative efficiency analysis uses comparative analysis of marginal product value and input prices. Economic efficiency analysis uses a combination of technical efficiency and allocative efficiency. The research results show that the average organic rice production in Sawit District is higher than the average inorganic rice production. Factors that significantly influence production levels are land area, seeds and fertilizer, while pesticides and labor do not significantly influence production levels because their use is not in accordance with needs. Organic and inorganic rice farming is approaching efficiency, where organic rice is technically more efficient than inorganic rice production but has not yet reached price and economic efficiency. It is recommended that in further research, other variables such as age and education can be added as well as analysis of farming development so that it can determine more appropriate decisions.